2007
DOI: 10.1002/app.25603
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extrusion, stretching and poling on the structural and piezoelectric properties of poly (vinylidene fluoride‐hexafluoropropylene) copolymer films

Abstract: Three types of poly (vinylidene fluoridehexafluoropropylene) (PVDF-HFP) copolymer films were prepared by extrusion, stretching as well as simultaneously stretching and static electric field poling (SSSEP), respectively, and measured by the differential scanning calorimetric, wide angle X-ray diffraction, fourier transformation infrared-attenuated total reflection, and Dynamic mechanical analysis. The experimental results showed that the films prepared by stretching and SSSEP have higher crystallinity and b pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…For instance, when electric field poling at 35 MV/m was chose as a point for comparison, the values of d 33 for poling samples are about five times in magnitude higher than the samples without electric field poling. The obtained d 33 values are almost the same order as those reported in the literatures, but the used electric field is much smaller [ 30 , 31 , 32 ]. The d 33 value of nanocomposites using the same experimental condition of electric field poling was higher than the data of pure PVDF matrix, which might be attributed to the incorporation of magnetite nanoparticles with negative surface charge.…”
Section: Resultssupporting
confidence: 81%
“…For instance, when electric field poling at 35 MV/m was chose as a point for comparison, the values of d 33 for poling samples are about five times in magnitude higher than the samples without electric field poling. The obtained d 33 values are almost the same order as those reported in the literatures, but the used electric field is much smaller [ 30 , 31 , 32 ]. The d 33 value of nanocomposites using the same experimental condition of electric field poling was higher than the data of pure PVDF matrix, which might be attributed to the incorporation of magnetite nanoparticles with negative surface charge.…”
Section: Resultssupporting
confidence: 81%
“…The samples were coated with silver paste prior to the piezoelectric experiments. Many studies observed the piezoelectric properties of PVDF-HFP and its nanocomposites, 53,54 but less attention was paid to the piezoelectric effect enhanced by lattice strain of the nanollers. 55 So far, the piezoelectric property of the composites was attributed to the b-phase fraction, ller dispersion and alignment of dipole moment.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…, where: A α and A β -are the heights of the peaks at 764 and 840 cm −1 , respectively, and the coefficient 1.26 represents the ratio of the absorption coefficients at 764 and 840 cm −1 [9][10][11].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%